Experiences and Challenges of Implementing Universal Health Coverage With China's National Basic Public Health Service Program: Literature Review, Regression Analysis, and Insider Interviews - Guixia Fang; Diling Yang; Li Wang; Zhihao Wang; Yuanyuan Liang; Jinxia Yang (JMIR Publications, 2022)
BackgroundPublic health service is an important component and pathway to achieve universal health coverage (UHC), a major direction goal of many countries. China's National Basic Public Health Service Program (the Program) is highly consistent with this direction. ObjectiveThe aim of this study was to analyze the key experience and challenges of the Program so as to present China's approach to UHC, help other countries understand and learn from China's experience, and promote UHC across the world. MethodsA literature review was performed across five main electronic databases and other sources. Some data were obtained from the Department of Primary Health, National Health Commission, China. Data obtained included the financing share of the national/provincial/prefectural government among the total investment of the program in 32 provinces in 2016, their respective per capita funding levels, and some indicators related to program implementation from 2009 to 2016. The Joinpoint regression model was adopted to test the time trend of changes in program implementation indicators. Face-to-face individual interviews and group discussions were conducted with 48 key insiders. ResultsThe program provided full life cycle service to the whole population with an equitable and affordable financing system, enhanced the capability and quality of the health workforce, and facilitated integration of the public health service delivery system. Meanwhile, there were also some shortcomings, including lack of selection and an exit mechanism of service items, inadequate system integration, shortage of qualified professionals, limited role played by actors outside the health sector, and a large gap between the subsidy standard and the actual service cost. The Joinpoint regression analysis demonstrated that 13 indicators related to program implementation showed a significant upward trend (P<.05) from 2009 to 2016, with average annual percent change values above 10% for 6 indicators and below 6% for 7 indicators. Three indicators (coverage of health records, electronic health records, and health management among the elderly) rose rapidly with annual percent change values above 30% between 2009 and 2011, but rose slowly or remained stable between 2011 and 2016. In 2016, the subsidy standard per capita in the eastern, central, and western regions was equivalent to US $7.43, $7.15, and $6.57, respectively, of which the national-level subsidy accounted for 25.50%, 60.57%, and 79.52%, respectively. ConclusionsThe Program has made a significant contribution to China's efforts in achieving UHC. The Program focuses on a key population and provides full life cycle services for the whole population. The financing system completely supported by the government makes the services more equitable and affordable. However, there are a few challenges to implementing the Program in China, especially to increase the public investment, optimize service items, enhance quality of the services, and evaluate the health outcomes.